Menatap Reformasi Pendidikan Nasional - Muhammad Rais (Al-Riwayah : Jurnal Kependidikan, 2017)
There are at least three factors that caused weaknesses of national education system: First, the education system is rigid and centralized. Second, the national education system does not ever consider the fact that there are in the community and addressing the people as mere objects of education. Third is the education bureaucracy system. At the same time, the mentality of universities should be improved. Universities should uphold academic integrity and ethics, including the freedom of academic forum and not be a rubber stamp for the legalization of injustice. Responsibility as a group of academic functioning and social agent of change of control should be actually enforced. The research conducted is above the rules of science, not on the basis of corruption in order to get funding. Colleges are educational institutions, research and public service that should be able to act in an objective and independent and always uphold the integrity of academic ethics. Academic autonomy should be embedded in each college to establish the truth (conscience), which in turn can improve intelligence, readiness of qualified human resources, and public welfare.